Dysbiosis of Gut Microbiota and Metabolite Phenylacetylglutamine in Coronary Artery Disease Patients With Stent Stenosis - Fang, Chen; Zuo, Kun; Fu, Yuan; Li, Jing; Wang, Hongjiang; Xu, Li; Yang, Xinchun (Frontiers in Cardiovascular Medicine, 2022)
Abstract Introduction: Dysbiotic gut microbiota (GM) plays a regulatory role during the pathogenesis of several cardiovascular diseases, including atherosclerosis. GM-derived metabolite phenylacetylglutamine (PAGln) enhances platelet responsiveness and thrombosis potential, thereby inducing major adverse cardiovascular events. However, the role of GM and microbial metabolite PAGln in the pathogenesis of in-stent stenosis remains unknown. Methods: 16S rRNA sequencing was performed on fecal samples in 103 coronary artery disease (CAD) patients, including 35 individuals with in-stent patency (control), 32 individuals with in-stent hyperplasia (ISH), and 36 subjects with in-stent stenosis (ISS), and the levels of plasma PAGln were evaluated by enzyme-linked immunosorbent assay. Results: The results revealed significantly enhanced microbial diversity and disrupted composition, such as enrichment of Roseburia, Blautia, and Ruminococcus, were observed in CAD patients with in-stent stenosis. The imbalance of microbial function related to PAGln synthesis and elevated plasma GM-derived metabolite PAGln levels was detected in CAD patients with in-stent stenosis. The GM-dependent diagnostic model could identify CAD patients with in-stent stenosis. Conclusions: The current study revealed the disordered signature, altered functions, and potential diagnostic ability of GM in CAD patients with in-stent hyperplasia and stenosis. Enhanced microbiota-derived PAGln synthesis-related functions and elevated plasma PAGln levels were associated with in-stent stenosis and hyperplasia in CAD patients. Thus, an intervention targeting gut microbes may be a promising strategy to prevent stent stenosis in patients with CAD.